Synthesis of Polyurethane/Silica Modified Epoxy Polymer Based on 1,3-Propanediol for Coating Application - Lutviasari Nuraini; Evi Triwulandari; Muhammad Ghozali; Muhammad Hanafi; Jumina Jumina (Indonesian Journal of Chemistry, 2017)
Studies on the synthesis of polyurethane/silica modified epoxy polymer using 1,3-propanediol has been conducted. Synthesis of polymers made by reaction of tolonate and 1,3-propanediol (ratio NCO/OH=2.5) as the building blocks of polyurethane with diglycidyl ether bisphenol A (DGEBA) epoxy and catalyst dibutyltin dilaurate (DBTL).The total weight of the polyurethane used was 20% (w/w) of the total epoxy. Based on Fourier Transform Infrared (FTIR) and 1H-Nuclear Magnetic Resonance (1H-NMR) spectra indicated the existence of a new bond that is formed from the reaction of isocyanate group and hydroxyl group, where the hydroxyl groups derived from epoxy and 1,3-propanediol. The addition of silica (5, 10, and 15% w/w to epoxy) into the epoxy-modified polyurethane has been carried out through sol-gel reaction of tetraethyl orthosilicate (TEOS). The isocyanate conversion rate for the addition of silica 5, 10, and 15% are 95.69; 100, and 100%, respectively. The morphology and element identification by Scanning Electron Microscopy/Energy Dispersive X-Ray Analysis (SEM/EDX), showed that Si element has been successfully added in the polymer. From the tensile strength and elongation analysis, also thermal stability analysis using Thermal Gravimetric Analyzer (TGA), the increase of silica amount into the polyurethane modified epoxy did not significantly affect to thermal properties, but decrease the tensile strength of the polymer.